Eficacia del método pilates aplicado en el tratamiento fisioterapeutico en pacientes con lumbagia mecánica comprendiendo en edades de 25 a 60 años del centro de rehabilitacion fisiocenter de la ciudad de quito en el periodo de diciembre del 2009 a mayo del 2010 - Asadovay Lema, Alexandra Paulina (2010)
These pages take us to a detailed form and he/she specifies of how to treat a patient with mechanical lumbalgia applying hot chemical compresses, massage and mainly the range of exercises that he offers the Method Pilates. This way we will check the effectiveness that on the whole achieves the treatment fisioterapéutico for the relief of the pain, to improve the muscular force and the flexibility of the lumbar column considering that in the lumbar area they are reflected the contracturas so common for the envelope use, about effort, nervous tensions or for bad work positions that they are born of this area but they are irradiated to a general uneasiness.